Improving Students' Reading Comprehension of Report Text with KWL Strategy - Farha, Nudiya Afiya; Rohani, Rohani (ELT Forum: Journal of English Language Teaching, 2019)
ABSTRACT This research was carried out to know the effectiveness of implementing KWL strategy to improve students’ reading comprehension of report text and to know whether there is a significant achievement difference between students who were taught with KWL strategy and those who were not. The instrument used was a multiple choice reading comprehension test. Seventy two eleventh graders of SMA Negeri 1 Bae Kudus were selected as the sample. They were divided equally into experimental and control group. The data collection involved pre-test, treatments, and post-test. The result of the implementation of KWL strategy in the experimental group improved the students’ participation, motivation, and interest during teaching and learning process. In addition, the results of pre-test and post-test showed that mean score of the experimental group had a higher increase from 74.58 to 90.97 than the control group (from 72.77 to 87.77). However, the Independent Sample Test showed there was no significant achievement difference between the students who were taught with KWL strategy and those who were not. (1.80) was higher than. Keywords: Quasi-experimental; KWL strategy; reading comprehension; report text